Life-History of the Seed-Corn Maggot, Hylemya cilicrura (Rond.) and of H. liturata (Mg.) (Diptera: Anthomyiidae) in Southwestern Ontario - Miller, L. A.; McClanahan, R. J. (The Canadian Entomologist, 1960)
The seed-corn maggot, Hylemya cilicrura (Rond.), infests a wide range of hosts in all provinces of Canada and is also a pest in the Yukon and the Northwest Territories. H. liturata (Meig.) frequently occurs in smaller numbers along with H. cilicrura. H. liturata has not ,been recorded from Alberta, Saskatchewan, and Manitoba (Brooks, 1951). Detailed accounts of the species have not been published by Canadian entomologists, though H. cilicrura has been known as a pest of cultivated crops in Canada for over 70 years. In southwestern Ontario the seed-corn maggot is one of the most serious soil pests of vegetables and field crops.